Periodontal disease and C-reactive protein : association with cardiovascular risk - Guimarães, Maria do Carmo Machado (2010)
Cardiovascular disease is the main cause of death in the contemporary western world and traditional risk factors do not completely explain its development. Plausible mechanisms have been proposed to explain the relationship between periodontal disease and cardiovascular disease, since both diseases present complex etiological factors, combining genetic and environmental influences. Several studies indicate that cell and molecular components of inflammatory and immunological events due to periodontal infection may contribute to develop cardiovascular disease. Among these components, C-reactive protein, an important acute phase reagent with pro-inflammatory properties, whose levels are high in periodontal infection and also a significant indicator of atherosclerosis may explain in part the association between periodontitis and cardiovascular disease. This protein and some other components of periodontal infection involved in this possible association are discussed in this revision of the literature. __________________________________________________________________________________________________________ RESUMO